4‐Thiouridine‐Enhanced Peroxidase‐Generated Biotinylation of RNA. (20th October 2020) - Huang, Jinguo; Zhao, Ruiqi; Qin, Shanshan; Yang, Shixi; Li, Wei; Mo, Jing; Wang, Fang; Du, Yuhao; Weng, Xiaocheng; Zhou, Xiang
Abstract: Peroxidase‐generated proximity labeling is in widespread use to study subcellular proteomes and the protein interaction networks in living cells, but the development of subcellular RNA labeling is limited. APEX‐seq has emerged as a new method to study subcellular RNA in living cells, but the labeling of RNA still has room to improve. In this work, we describe 4‐thiouridine (s 4 U)‐enhanced peroxidase‐generated biotinylation of RNA with high efficiency. The incorporation of s 4 U could introduce additional sites for RNA labeling, enhanced biotinylation was observed on monomer, model oligo RNA and total RNA. Through the s 4 U metabolic approach, the in vivo RNA biotinylation efficiency by peroxidase catalysis was also dramatically increased, which will benefit RNA isolation and study for the spatial transcriptome. Abstract : Subcellular, not substandard : A 4‐thiouridine‐enhanced RNA proximity biotinylation method that combines peroxidase‐mediated catalysis and s 4 U metabolic strategy has been developed to significantly enhance the efficiency of peroxidase‐generated RNA labeling. This method is easy to operate, benefitting RNA isolation and the study of the spatial transcriptome.